The Problem of Institutional Corruption in the System of Higher Education - E. I. Trubnikova; D. A. Trubnikov (Высшее образование в России)
The article analyzes modern problems and trends of development of the system of higher education. The persistent expansion of regulation and uncontrolled growth of bureaucracy increase dependence of regulated areas on private interests of those who have access to the regulatory machine. This tendency has not bypassed the academic sphere, and, in many instances, there is a clear discrepancy between the proclaimed objectives and observed results. The vivid example is the Russian system of higher education, which is the main focus of the present study. We explain this phenomenon through the lens of the institutional corruption theory and argue that the observing evolution of modern academia forms a wrong system of incentives, bringing to the hands of bureaucrats excessive power, which, eventually, distorts the performance of the higher education sphere and undermines the effectiveness of this important institution.